Pax Latex Exhibits Wound-Healing Effect in Normal and Diabetic Mice - Ana Bertha Hernandez-Hernandez PhD; Francisco Javier Alarcon-Aguilar PhD; Mario Garcia-Lorenzana PhD; Marco Aurelio Rodriguez-Monroy PhD; Maria Margarita Canales-Martinez PhD (SAGE Publishing, 2021)
Jatropha neopauciflora is an endemic species of Mexico. Its latex is used to treat wounds, scarring, oral infections, and loose teeth. To date, there are no studies that validate at a morphological level a wound-healing use in diabetes. The present research aimed to evaluate the wound-healing capacity of the latex of J. neopauciflora in the skin of healthy and streptozotocin-induced diabetic mice. Also, a chemical analysis of the latex through molecular exclusion chromatography and HPLC were performed. Male mice ( Mus musculus ) of 7-week-old CD1 strain were used. Groups of healthy and diabetic mice were formed. A longitudinal cut of 1 cm was performed on the depilated skin. All treatments were topically applied to the wound area twice a day for ten days. At the end of the experiments, the skin sections were obtained from the wound area and stained with Hematoxylin-Eosin. Then we counted the number of active fibroblasts in all the experimental groups. In normal mice, the latex accelerated the wound-healing process and decreased the number of active fibroblasts, similarly to Recoveron. In diabetic mice, the latex and Recoveron increased the number of active fibroblasts. In normal and diabetic mice, a thin and orderly epidermis was observed. Molecular exclusion chromatography exhibited 58 fractions, 14 of which were subjected to HPLC, to detect catechin, a flavonoid with antioxidant, antimicrobial, and anti-inflammatory properties. J. neopauciflora latex can be useful for wound treatment in patients with diabetes mellitus because it accelerates and promotes the wound-healing process.